2014
DOI: 10.1590/0074-0276130397
|View full text |Cite
|
Sign up to set email alerts
|

Good agreements between self and clinician-collected specimens for the detection of human papillomavirus in Brazilian patients

Abstract: Women infected with human papillomavirus (HPV) are at a higher risk of developing cervical lesions. In the current study, self and clinician-collected vaginal and cervical samples from women were processed to detect HPV DNA using polymerase chain reaction (PCR) with PGMY09/11 primers. HPV genotypes were determined using type-specific PCR. HPV DNA detection showed good concordance between self and clinician-collected samples (84.6%; kappa = 0.72). HPV infection was found in 30% women and genotyping was more con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Several studies have been conducted around Brazil. The prevalence rates range from 10·5% to 48·6% [19][20][21][22][23][24][25][26][27]. In this study, we detected a high prevalence of HPV infection in Southern Bahia (47·7%, 95% CI 40·8-54·7), which is similar to the prevalence reported in Rio de Janeiro [27], and higher when compared with other regions including Salvador, the Capital of Bahia State [23,28].…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have been conducted around Brazil. The prevalence rates range from 10·5% to 48·6% [19][20][21][22][23][24][25][26][27]. In this study, we detected a high prevalence of HPV infection in Southern Bahia (47·7%, 95% CI 40·8-54·7), which is similar to the prevalence reported in Rio de Janeiro [27], and higher when compared with other regions including Salvador, the Capital of Bahia State [23,28].…”
Section: Discussionsupporting
confidence: 78%
“…We believe that this strategy could improve the poor screening programs developed in our country. Not only the HPV DNA detection rate in self-sampling has been reported to be in good agreement with physician-sampling, but also the self-sampling method seems better accepted among women [24, 25]. It could therefore enhance cervical cancer screening program coverage, a primary prevention strategy in countries with low resources [26].…”
Section: Discussionmentioning
confidence: 99%
“…HPV-induced cell transformation is mediated by the viral E6 and E7 oncoproteins interfering with the cell cycle regulators of the host cells, starting at the basal cells layer and gradually extending to the full epithelial thickness [ 9 , 18 ]. Once the infection is well established, the HPV genome is present as extra-chromosomal elements (episomes) in the nucleus, and the viral genome load is increased up to 50–100 copies per cell, while remaining high in the infectious phase [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, self-collection of vaginal specimens for HPV testing could be useful particularly for women who live in regions with low-resource settings and restricted access to adequate health care, like in many regions of Brazil, thus increasing the acceptability and coverage of the screening program. However, HPV DNA testing is not yet a routine in Brazil, despite the fact that several studies in Brazilian population have demonstrated its potential usefulness in CC prevention [ 20 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%